2016
DOI: 10.1111/padm.12282
|View full text |Cite
|
Sign up to set email alerts
|

Targets for Honesty: How Performance Indicators Shape Integrity in Dutch Higher Education

Abstract: Universities across the world have recently experienced a number of serious cases of academic misconduct. In the public and academic debates, one dominant explanation exists for the fraudulent behaviour of university staff. Academic misconduct is considered to be the logical behavioural consequence of output‐oriented management practices, based on performance incentives. This article puts this explanation to the test. Based on our analysis of a dataset of employees in Dutch higher education (N = 4,775) from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…"Academic misconduct is considered to be the logical behavioral consequence of outputoriented management practices, based on performance incentives." [44] (p. 1140).…”
Section: Theoretical Background: Explanations For Misconductmentioning
confidence: 99%
“…"Academic misconduct is considered to be the logical behavioral consequence of outputoriented management practices, based on performance incentives." [44] (p. 1140).…”
Section: Theoretical Background: Explanations For Misconductmentioning
confidence: 99%
“…The items reported for the framework of Bennett and Robinson (2000) are from the subscale 'organizational deviance,' which includes the behaviors of the former category 'production deviance' is negatively related to scholarly performance, whereas Lewis (2014) concludes that there is no relationship between scientists' attitudes toward performance measurement and their publication performance. Overman et al (2016) found a positive relationship between the specificity of performance contracts (i.e., the extent to which there are concrete and detailed agreements on performance targets regarding results and rewards) and the level of integrity (i.e., conforming to norms) that academics perceive at their workplace. Both studies, Lewis (2014) and Overman et al (2016), focused on the positive consequences of increasing the use of performance measurement practices in academia.…”
Section: Limitations and Future Researchmentioning
confidence: 98%
“…Overman et al (2016) found a positive relationship between the specificity of performance contracts (i.e., the extent to which there are concrete and detailed agreements on performance targets regarding results and rewards) and the level of integrity (i.e., conforming to norms) that academics perceive at their workplace. Both studies, Lewis (2014) and Overman et al (2016), focused on the positive consequences of increasing the use of performance measurement practices in academia. This viewpoint is not only consistent with our finding that performance measurement practices have positive as well as negative effects on scientists' behavior, but it is also in line with the extensive research on the positive effects of goal setting on performance (e.g., Locke 1990, 1991;Latham 2002, 2006).…”
Section: Limitations and Future Researchmentioning
confidence: 98%
“…When this happens, it can lead to corrupt individuals. Overman et al (2016) seem to subscribe to this proposition when they write: "Academic misconduct is considered to be the logical behavioral consequence of output-oriented management practices, based on performance incentives." (p. 1140).…”
Section: Six 12 : Ethos Of Public Administrationmentioning
confidence: 99%